Une « banlieue créative » dans le Grand Paris ? - Boris Lebeau (EchoGéo)
The community of Plaine Commune is implementing a project of a « territory of culture and creation » within the Grand Paris. It is a completely original version of the concept of a creative city, set in a deprived suburb. Indeed, its designers liken social fringe to creativity and in doing so they question the place that these poorer districts could hold within a cultural and creative economy in the future. We'll draw distinctions between what is political, what is territorial marketing, and what is the socio-economic functioning of the territory and we will study what impact such a proposal can have.